Penanaman dan Penguatan Nilai-Nilai Keislaman Melalui Perayaan Hari Besar Islam - Eddy Saputra; Ahmad Muhajir (Al Ashriyyah, 2019)
Islam in indonesia develops very rapidly. Culture a to make infrastructure islamic teachings if received by the easy.Islamic can survive through tradition peringantan one a day developed by the clergy not before.Can be can be made by media refreshment in improving in values of islamic teachings, knowledge of islamic unmannerly value reflected in to in implementasikan in daily life.Perayaran a day is the concept to non formal education islamic values.The research uses the qualitative method.Technique data collection is in some literasi pertaining research and literature.Achieved results a day on a research that islamic faith and strengthening capable of increase faith and increase tolerance among the people someone religion.